The Wrong boy - Russell, Willy (London : Black Swan, 2001)
The Dewsbury Desperadoes are on their way to Pontefract for a gig at the Allied Butchers' & Architects' Club. The Girl with the Chestnut Eyes is on her way to somewhere. And Raymond is heading for Gulag Grimshy. Raymond Marks is a normal boy, from a normal family, in a normal northern town. His dad left home after falling in love with a five-string banjo; his fun-hating grandma believes she should have married Jean-Paul Sartre: '1 could never read his books, but y' could tell from his picture, there was nothing frivolous about John-Paul Sartre.' Felonious Uncle Jason and Appalling Aunty Paula are lusting after the satellite dish; frogs are flattened on Failsworth Boulevard; and Sickening Sonia's being sick in the majestic cathedral of words. Raymond Marks is a normal boy, from a normal family, in a normal northern town. Until, on the banks of the Rochdale Canal, the Flytrapping craze begins and, for Raymond and his mam, nothing is ever quite so normal again.
Keywords: England, Northern -- Social life and customs -- Fiction